2017
DOI: 10.1080/87565641.2017.1401628
|View full text |Cite
|
Sign up to set email alerts
|

Texas Mexican American adult normative studies: Normative data for commonly used clinical neuropsychological measures for English- and Spanish-speakers

Abstract: This study aimed to provide normative references for Mexican Americans on neuropsychological measures of cognitive functioning. Data were analyzed from a total of 797 Mexican-Americans recruited across three Texas-based studies with approximately one-half of the participants tested in Spanish. Normative tables include: MMSE, AMNART, WMS-III (Logical Memory I, II; Visual Reproduction I, II; Digit Span), CERAD, RAVLT, Exit25, CLOX 1 & 2, Trail Making Test- A&B, BNT, COWA, and Animal Naming. The norms were strati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 66 publications
7
37
1
Order By: Relevance
“…In terms of the effects of education on the LM scores, our findings were consistent with the findings from the previous studies [13-17,23,24], which showed that poorer performances on the LM subtest were observed in less educated group. In Danish and Italian studies, there was a significant effect of education on performances on the LM [15,16].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In terms of the effects of education on the LM scores, our findings were consistent with the findings from the previous studies [13-17,23,24], which showed that poorer performances on the LM subtest were observed in less educated group. In Danish and Italian studies, there was a significant effect of education on performances on the LM [15,16].…”
Section: Discussionsupporting
confidence: 92%
“…In Danish and Italian studies, there was a significant effect of education on performances on the LM [15,16]. In a Mexican-American study, the level of education was the strongest demographic predictor of the LM I and II performances [17]. A previous study that estimated the influence of education on the LM test in the Korean version of WMS-IV among adults aging between 16 and 69 showed that education was an important determinant for the LM subtest scores and its influence on the LM performance increased as participants got older [24].…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive tests scores used for analysis were scale scores stratified by education and age that were generated for Texas-based Mexican-Americans. [24] Significant differences were indicated when the 2-sided P values were less than .05. The data were analyzed by SPSS version 22 for Windows (SPSS Inc., Chicago, IL).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, when using these tests to estimate the five factors in our model, it is necessary to use CFA to avoid the potentially biasing effects of measurement error. Failing that, application of demographically corrected normative data to the observed scores may help attenuate the effects of systematic bias on the observed test results to some extent [48,49].…”
Section: Discussionmentioning
confidence: 99%